Eradication of Helicobacter pylori and Gastric Cancer: A Controversial Relationship - Piscione, Mariagrazia; Mazzone, Mariangela; Di Marcantonio, Maria Carmela; Muraro, Raffaella; Mincione, Gabriella (Frontiers in Microbiology, 2021)
Worldwide, gastric cancer (GC) represents the fifth cancer for incidence, and the third as cause of death in developed countries. Indeed, it resulted in more than 780,000 deaths in 2018. Helicobacter pylori appears to be responsible for the majority of these cancers. On the basis of recent studies, and either alone or combined with additional etiological factors, H. pylori is considered a “type I carcinogen.” Over recent decades, new insights have been obtained into the strategies that have been adopted by H. pylori to survive the acidic conditions of the gastric environment, and to result in persistent infection, and dysregulation of host functions. The multistep processes involved in the development of GC are initiated by transition of the mucosa into chronic non-atrophic gastritis, which is primarily triggered by infection with H. pylori. This gastritis then progresses into atrophic gastritis and intestinal metaplasia, and then to dysplasia, and following Correa’s cascade, to adenocarcinoma. The use of antibiotics for eradication of H. pylori can reduce the incidence of precancerous lesions only in the early stages of gastric carcinogenesis. Here, we first survey the etiology and risk factors of GC, and then we analyze the mechanisms underlying tumorigenesis induced by H. pylori, focusing attention on virulence factor CagA, inflammation, oxidative stress, and ErbB2 receptor tyrosine kinase. Moreover, we investigate the relationships between H. pylori eradication therapy and other diseases, considering not only cardia (upper stomach) cancers and Barrett’s esophagus, but also asthma and allergies, through discussion of the “hygiene hypothesis. ” This hypothesis suggests that improved hygiene and antibiotic use in early life reduces microbial exposure, such that the immune response does not become primed, and individuals are not protected against atopic disorders, asthma, and autoimmune diseases. Finally, we overview recent advances to uncover the complex interplay between H. pylori and the gut microbiota during gastric carcinogenesis, as characterized by reduced bacterial diversity and increased microbial dysbiosis. Indeed, it is of particular importance to identify the bacterial taxa of the stomach that might predict the outcome of gastric disease through the stages of Correa’s cascade, to improve prevention and therapy of gastric carcinoma.